Prevalence and correlates of stunting among a high-risk population of Kenyan children recently hospitalized for acute illnesses - Atlas, Hannah E.; Brander, Rebecca L.; Tickell, Kirkby D.; Bunyige, Lucy; Oongo, Susan; McGrath, Christine J.; John-Stewart, Grace C.; Richardson, Barbra A.; Singa, Benson O.; Denno, Donna M.; Walson, Judd L.; Pavlinac, Patricia B. (American Society of Tropical Medicine and Hygiene, 2024)
Stunting (length/height-for-age z-score < –2) is associated with significant morbidity and mortality among children under 5 years of age in sub-Saharan Africa. Children who are stunted and recently hospitalized for acute illness may be at particularly elevated risk for post-discharge mortality. In this cross-sectional analysis, we measured the prevalence of stunting at hospital discharge and identified host, caregiver, and environmental correlates of stunting among children aged 1–59 months in Western Kenya enrolled in the Toto Bora Trial. Child age- and site-adjusted prevalence ratios were estimated using Poisson regression. Of the 1,394 children included in this analysis, 23% were stunted at hospital discharge. Older children (12–23 months and 24–59 months versus 0–5 months) had a higher prevalence of stunting (adjusted prevalence ratio [aPR]: 1.58; 95% CI: 1.04–2.36 and aPR: 1.59; 95% CI: 1.08–2.34, respectively). HIV-exposed, uninfected children (aPR: 1.94; 95% CI: 1.39–2.70), children with HIV infection (aPR: 2.73; 95% CI: 1.45–5.15), and those who were never exclusively breastfed in early life (aPR 2.51; 95% CI: 1.35–4.67) were more likely to be stunted. Caregiver education (primary school or less) and unimproved sanitation (pit latrine without slab floor or open defecation) were associated with increased risk of stunting (aPR: 1.94; 95% CI: 1.54–2.44; aPR: 1.99; 95% CI: 1.20–3.31; aPR: 3.57; 95% CI: 1.77–7.21, respectively). Hospital discharge represents an important opportunity for both identifying and delivering targeted interventions for nutrition-associated poor outcomes among a high-risk population of children.